Józef Tischner's Debate with Thomism - Between Confrontation and Dialogue - Jawor, Marek (Filozofia Chrześcijańska, 2013)
The article presents an analysis of Józef Tischner’s debate with Thomism. Leaving aside the historical and personal influences which shaped the debate, the author is trying to assess the presented polemics on two fundamental planes: metatheoretical and anthropological. The text constitutes an attempt to answer the question: are the two disparate approaches bound to remain seen as ever confronting, or is there a possibility of them entering a constructive dialogue?